Correlation between foodborne pathogens and murine contamination of red pepper powder. (March 2021) - Lee, Hee-Min; Park, Boyeon; Yang, Ji-Su; Ha, Ji-Hyoung
Abstract: Food contamination—especially by rodents—may cause microbial infections when consumed. Various spices contaminated with rodent fecal matter or hair, and several pathogenic microorganisms are often detected in the same spice sample. As such, it is imperative to constantly monitor contamination levels in food. Herein, we investigated the efficacy of two DNA extraction kits and ultimately used the DNeasy® mericon® Food Kit to monitor the contaminant levels associated with murine substances in 56 red pepper powder samples. We tested the samples for Escherichia coli O157, Staphylococcus aureus, Listeria monocytogenes, and Salmonella spp. Using quantitative polymerase chain reaction. The Ct values of the samples were between 30 and 36. No significant fluorescence (Ct > 37) was detected in any samples. Murine DNA was detected in 30.3% of samples comprising six domestic and 11 imported red pepper powders and in 68.7% of the imported samples; 47.1% of samples with murine contamination tested positive for S. aureus . Our findings suggested that red pepper powder contaminated with murine substances likely contains S. aureus, which may potentially influence the health of consumers. Hence, these results may serve as a reference for members of the food industry aiming to improve food safety and quality. Highlights: The DNeasy® mericon® Food Kit was an efficient DNA extraction tool. Murine DNA was detected in 30.3% of red pepper powder samples. Murine DNA was detected in 68.7% of imported samples. Staphylococcus aureus was detected in 47.1% of murine-contaminated samples.